ANTROPOLOGISKE KRUMSPRING I ET VIDENSSAMFUND: Om at lave feltarbejde i en agora - Brichet, Natalia; Nielsen, Gritt Bykærholm (Tidsskriftet Antropologi, 2006)
Taking its point of departure in their recent fieldwork, the authors explore the concept of knowledge in two different ways. How is scientific knowledge conceived in the debate surrounding the passage of the new Danish legislation on universities? And how is it possible to work with knowledge in the form of humanistic research as object of anthropological enquiry? In anthropology, knowledge, in relation to research has especially been studied regarding the natural sciences, i.e. in laboratories. The authors see this as a logical consequence of the development in anthropological method and theory, where the anthropological object has increasingly been defined as an object with a specific physical integrity – that is, as tied to a group of people and/or a physical place. This discussion finds an interesting parallel in the debate of the new act. Scientific knowledge is by some humanistic researchers understood as a solitary process where demands from larger society, as well as from the institutional community are considered restrictive, a factor that potentially pollutes the otherwise pure science. Thereby science is perceived as a relatively autonomous field in society – quite similar to the classic notion of culture. Arguing for an actor-network, dialogic notion of the anthropological field, i.p. as an agora, requires a “rhizomatic” form of knowledge for humanistic research in general and anthropological research in particular.